Content validity of circuit training program and its effects on the aerobic endurance of wheelchair tennis athletes - Yulianto, W. D.; Yudhistira, D. (International Journal of Kinesiology & Sports Science, 2021)
Background: "Exercise is an activity to improve technical and physical competence of athletes", most sports require an excellent physical aspect to win. Aerobic endurance is an essential point in the preparation of a wheelchair tennis training program. Aim: This research is to validate the circuit training program and test the exercise program on the aerobic endurance of wheelchair tennis athletes. Method: This research is development research with qualitative and quantitative approaches. Participants are wheelchair tennis athletes with ten males and four females, height 156-167± cm, weight 50-70± kg, age 31-35. Participants in the program validation were seven nationally licensed physical fitness trainers. The first stage qualitatively examines documents in articles, ebooks, textbooks to design the program. The second stage quantitatively applies the Delphi technique to assess the prepared training program. The third stage analyzes the assessment results with the content validity ratio formula and, the fourth stage tests the exercise program for six weeks. The instrument used is a multistage fitness test. Results: It has been found that the assessment items from seven experts show the content validity ratio value is 1.00, so it can be categorized as having good content validity. It has been found the mean posttest (N=14, M=249.14, SD=16.033) and posttest (N=14, M=241.71, SD=17.166). It has been found that hypothesis testing using paired samples t-test analysis (p=0.000<0.05). Conclusion: the circuit training exercise program has good validity, then based on the effectiveness test, there is an increase in the aerobic endurance of wheelchair tennis athletes.